Is It Possible to Prevent Radicalism through Women's Participation in STEM (Science, Technology, Engineering, and Mathematics) Education?: Challenges and Opportunities - Imaduddin, Muhamad (UIN Sunan Kudus, 2020)
Women and education as an effort to prevent radicalism are connected. If the international community tries to engage education as part of a strategy to reduce terrorism, it should be necessary to consider the content of education. One of the SDGs mandates in “equality” is the importance of women to be involved in mastering STEM. This study reveals how the challenges and opportunities for women's relationships and participation in STEM education can make it possible to prevent the emergence of radicalism. This was carried out by exploring several kinds of literature related to the level of women's participation and the usefulness of STEM education. The role of women is shown by their participation as learners, educators, and directly involved in the STEM industry as a workforce. As an educator, women's participation occupies a much better position than workforces. STEM content can be integrated with radicalism issues to be resolved in the classroom to practice critical thinking skills. Women as STEM workers face obstacles that have nothing to do with their abilities, such as stereotyping, discrimination, violence, and abuse. Religious education integrated with STEM education provides an opportunity to reduce radicalism values with women taking part in it.